Resolution of dual residence instances in the case of companies - Živković Lidija (Anali Pravnog Fakulteta u Beogradu)
The application of double taxation treaties presupposes that the potential cases of dual residence have been previously resolved. For this purpose, the major model-conventions on the basis of which double taxation treaties around the globe are negotiated contain the so-called tie-breaker rule. In the wake of the recent revision of the international tax system resulting from the OECD's Base Erosion and Profit Shifting Action Plan, the existing tie-breaker rule for companies has been thoroughly amended. Instead of determining companies' residence based on the place of the effective management criterion, the new approach stipulates that such cases will be decided through the application of the Mutual Agreement Procedure, between the competent authorities of the relevant contracting states. After outlining the historical development of the said mechanism in the context of dual residence resolution, this article purports to critically assess its desirability, with a special focus on its implementation in Serbia.